Discharge capacity of shaft spillway with a polygonal section: a case study of Djedra dam (East Algeria) - Kahlerras Djillali (IWA Publishing, 2021)
This paper proposes a new design for the shaft spillway of the Djedra dam (East Algeria). The procedure consists of replacing the circular section with a polygonal configuration of twelve (12) sections. The study of the model was divided into five different versions according to the variants of technical modifications of the water intake funnel; this configuration was tested on a hydraulic model in the laboratory of hydroelectric power plants of the Moscow State University of Environmental Engineering. The use of the polygonal section weir can greatly simplify the formwork of the structure, also the free entry funnel increases the discharge coefficient by 20%, without exposing the head of the weir to the risk of cavitation. In the event of submersion, the adopted design can ensure the crossing of an estimated relative flow with a probability of P = 0.01%, which means reducing the height of the dam by 0.68 m, and thus making the hydraulic structure more efficient economically and more reliable. The experimental model was produced on a 1:60 scale of the prototype, which guarantees self-simulation of the hydraulic phenomena of the Djedra dam, and its final design is judged to be hydraulically satisfactory and recommended for construction. HIGHLIGHTS A new design of the weir of the dam is a polygonal configuration.; The polygonal section weir simplifies its structure.; The free entry weir funnel increases the discharge coefficient by 20%.; In the event of submersion, the weir provides an estimated flow rate of P = 0.01%.; The experimental model produced on a scale of 1:60 of the prototype guarantees self-simulation of the hydraulic phenomena of the dam.;